Socio-technological responses to COVID-19 in Mexico: Spin-offs, repositories and 3D printing - Matus Ruiz, Maximino (Noesis. Journal of Social Sciences and Humanities, 2023)
The objective of the article is to analyze two sociotechnical initiatives, one citizen and the other governmental, that were configured in Mexico as a response to the shortage and hoarding of medical devices in the context of the COVID-19 pandemic. The citizen response analyzed is the coronavirus_maker_mx movement, while the governmental initiative under scrutiny are the Gätsy and Ehecátl 4T ventilators developed under the coordination of the National Council on Science and Technology. The methodology used involved online tracking of coronavirus_maker groups, open interviews with community members, and review of second-hand sources in the case of the government initiative. By unraveling the networks of actors that were behind the design and production or printing of devices to address COVID-19, we conclude that the cases analyzed represent different models of technological development that invite us to think about some alternatives for the promotion of "sovereign" technology in Mexico.